1999
DOI: 10.2337/diabetes.48.2.416
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphism in the NeuroD/BETA2 gene with type 1 diabetes in the Japanese.

Abstract: NeuroD/BETA2, a transcription factor of the insulin gene, also plays an important role in the development of pancreatic beta-cells. Recently, the NeuroD/BETA2 gene has been mapped to the long arm of human chromosome 2 (2q32) where the IDDM7 gene has previously been mapped, implying its involvement in diabetes. To identify mutations in the NeuroD/BETA2 gene that may predispose patients to develop diabetes, we studied the gene in 50 Japanese subjects with diabetes (4 with type 1 and 46 with type 2) by the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 0 publications
2
35
2
Order By: Relevance
“…Dupont et al (17) suggested an ethnic difference between Caucasians and Japanese because no AA homozygote was found in a previous study in Japanese (11). However, in our study, we did find AA homozygotes in both type 1 diabetes and control subjects (10.5 and 3.3%, respectively) in the Japanese population.…”
Section: Statistical Analysescontrasting
confidence: 56%
See 2 more Smart Citations
“…Dupont et al (17) suggested an ethnic difference between Caucasians and Japanese because no AA homozygote was found in a previous study in Japanese (11). However, in our study, we did find AA homozygotes in both type 1 diabetes and control subjects (10.5 and 3.3%, respectively) in the Japanese population.…”
Section: Statistical Analysescontrasting
confidence: 56%
“…It is known that there is a G3 A transition polymorphism in codon 45 of the NeuroD/BETA2 gene, leading to an Ala/Thr substitution in the NH 2 -terminus, although the functional difference between the G and A alleles is unknown. Previously, several studies showed no association between this gene and type 1 diabetes (16,17), whereas one study showed a significant association (11). Therefore, the role of this gene in type 1 diabetes is controversial and inconclusive.…”
Section: Statistical Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of BETA2 is highlighted by the discovery that it is the sixth maturity-onset diabetes of the young (MODY6) gene identified (24). In addition, many genetic studies in various populations have linked mutations in BETA2 to susceptibility to type 1 (25)(26)(27) and type 2 (28,29) diabetes. Consequently, target genes of BETA2 will likely affect the etiology of diabetes linked to BETA2.…”
Section: Discussionmentioning
confidence: 99%
“…These include genes of the interleukin-1 gene cluster (ie IL1R1, [144][145][146] IL1B, 130,147,148 and IL1RN 130,149 ) HOXD8, 150 GAD1, 151 GALNT3, 141 and NEUROD. [152][153][154] However, linkage or association has not been convincingly demonstrated for any of these candidate genes.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%